EVALUASI SISTEM PEMBINAAN, PENATAUSAHAAN, DAN PENGAWASAN PENGELOLAAN BARANG MILIK DAERAH PADA BPK-BMD DI PEMERINTAHAN KABUPATEN MINAHASA - Sumual, Astrid Claudia; Saerang, David Paul Elia; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The management of local asset is part of the regional financial management. Since the enactment of regulation of asset management area is expected to be a reference and strength of local government in managing its regional asset. To apply the system in accordance with Permendagri No.19 year 2016 supervision and coorperation required to carry out the process of recording asset at SKPD level as well as management of regional assets including BPK BMD Minahasa district. The purpose of this study is to find out how the application on the system of coaching, administration, and supervision of goods in the management of local assets in BPK BMD Minahasa whether in accordance with Permendagri No.19 year 2016. The method used in this research is descriptive qualitative analysis method. The results showed that the implementation management of local asset, especially the coaching, administration, and supervision of assets in BPK BMD Minahasa accordance with Permendagri No.19 yaers 2016. Not yet supported IT equipment that has not been compatible with that asset user and the lack of human resources becomes an obstacle asset management in BPK BMD Minahasa.Keywords: asset, coaching, administration, supervision